Analysis of Cryptocurrency Using a Genetic Algorithm (GA) - Yulius Eka Agung Seputra (Proceedings, 2023)
Finance, in particular, is tightly correlated with information-technology development. Digital currency or cryptocurrency is the outcome of the advancement of financial technology. As a means of payment over the internet, digital currencies are beginning to be widely used. This currency was developed in order to facilitate and secure transactions. Transaction fees have decreased as a result of the adoption of blockchain technology. Because it has a negative effect on the financial system, monetary stability, and payment system, government policy forbids transactions involving cryptocurrencies. Understanding of the stochastic and genetic algorithm models used in cryptocurrency is provided by this research. Cryptocurrency is a financial technological advancement that is part of the technological package and it enables banknotes to be replaced in financial transactions. A genetic algorithm (GA) achieved an MSE value of 0.0863 and an MPE of 0.0084 with data on cryptocurrencies. The aim of this research was that, in the future, the government would support cryptocurrency technology so that the laws that are passed preserve the Indonesian market while not forbidding anything outright.